1982
DOI: 10.21273/jashs.107.6.1046
|View full text |Cite
|
Sign up to set email alerts
|

Role of Light Quality, Photoperiod, and High-intensity Supplemental Lighting on Flowering of Alstroemeria ‘Regina’1

Abstract: Alstroemeria L. ‘Regina’ plants grown at 22°C did not flower, regardless of photoperiod treatments. If grown at 13°, plants flowered sooner under long photoperiod treatments than under natural days (ND). Incandescent (Inc) or red light treatments applied as a night interruption (NI) promoted earlier flowering than NI-far-red, ND, or short days (SD). Number of flowering shoots was unaffected by light quality. Plants grown under SD treatments produced the fewest flowering shoots. Flower production was related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Although researchers have investigated the effect of alternating temperatures (10,15), constant low air temperatures (4,5,7,13,14,15), or high air temperatures (4,5,8,13,14) on growth and flowering of alstroemeria, no one yet has shown a definite relationship between controlled soil temperature and floral induction (Table 1) or soil/air temperature X photoperiod with flower induction and generative shoot production of Alstroemeria 'Regina' (Table 2). Lin (11) reported that circulating 10°C tap water in pipes 25 cm below the soil surface increased spring-summer production, and a 16-hr high-pressure sodium lighting regime reduced flowering.…”
Section: Soil Temperaturementioning
confidence: 99%
See 3 more Smart Citations
“…Although researchers have investigated the effect of alternating temperatures (10,15), constant low air temperatures (4,5,7,13,14,15), or high air temperatures (4,5,8,13,14) on growth and flowering of alstroemeria, no one yet has shown a definite relationship between controlled soil temperature and floral induction (Table 1) or soil/air temperature X photoperiod with flower induction and generative shoot production of Alstroemeria 'Regina' (Table 2). Lin (11) reported that circulating 10°C tap water in pipes 25 cm below the soil surface increased spring-summer production, and a 16-hr high-pressure sodium lighting regime reduced flowering.…”
Section: Soil Temperaturementioning
confidence: 99%
“…The exact control mechanisms for Alstroemeria 'Regina' flower induction, initiation, and development are not clearly understood (4,5,6,7,8). Several workers have shown the influence of air temperature on generative alstroemeria shoot induction and subsequent shoot and flower development (3,5,6,7,9,10,14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In winter, only plants treated with the combination of soil cooling and HPS lighting produced flowers.Recent research on Alstroemeria (Lily-ofthe-Incas) flowering has been devoted to its earliness (3, 4). Early flowering increases the production span and thereby productivity, because all Alstroemeria plants cease flow ering at about the same time, regardless of previous photoperiod treatments (5).Temperature and light have been studied previously with regard to Alstroemeria flow ering (1,3,4,9). It has been suggested that Alstroemeria flowering involves a phasic mechanism in which thermophase precedes photophase (3).…”
mentioning
confidence: 99%